Creating Motivation for Local Thai Gastronomy Tourism to Strengthen Immunity in the Way of a Healthy Community after Covid-19 Pandemic.: การสร้างแรงจูงใจในการท่องเที่ยวเชิงอาหารไทยท้องถิ่นเสริมภูมิต้านทานในวิถีชุมชนสุขภาพ หลังการแพร่ระบาดของไวรัส Covid-19 - Chunkajorn, Puri (Journal of Faculty of Humanities and Social Sciences Thepsatri Rajabhat University, 2020)
This academic article is to study the motivation of tourists in local Thai gastronomy tourism, ways of community health. The motivation of tourists is the purpose of eating food to affect health in the beginning of the year 2020, tourists from around the world have been affected by health from the outbreak of the virus that occurs around the world. Causing tourists to turn their attention to health tourism clearly tourists consider that food tourism in Thailand is a good way to improve health through nutritious food. Comes from the famous Thai herbs in order to prevent or treat various diseases, therefore, the joint arrangement between local Thai gastronomy tourism, healthy community ways to be effective and well-known among Thai and foreign tourists is Must come from the cooperation of the people in the community to present a variety of ingredients for cooking. Variety of Thai food in each area Thai cooking methods by using local ingredients as the main selling point in determining local tourism food activities in parallel with Thai health tourism.